PENGARUH CAPITAL STRUCTURE, COMPANY GROWTH DAN PROFITABILITY TERHADAP COMPANY VALUE PADA PT PERUSAHAAN GAS NEGARA TBK PERIODE 2012-2024 - Astutik, Endang Puji (Yayasan Education and Social Center, 2026)
This research was conducted with the aim of examining the effect of Current Ratio (CR), Debt to Equity Ratio (DER), on Return On Equity (ROE) in PT Telekomunikasi Indonesia (Persero) Tbk company. Data obtained through www.idx.co.id in form of financial reports that have been prepared by PT Telekomunikasi Indonesia (Persero) Tbk.This research uses a quantitative descriptive method with a sample of 10 years, namely inthe form of annual financial reports for the period 2012-2021. The data analysis used is multiple linear regression analysis using SPSS ver.27 software for windows. Hypothesis testing using the t test, f test, and determination test. The results showed that Current Ratio (CR) has a positive and significant partial effect on Return On Equity (ROE) with a tcount value of 2.994 > 2.365 ttable and has a significance value of 0.017 < 0.05 and Debt to Equity Ratio (DER) has a negative and significant partial effect on Return On Equity (ROE) with atcount value of -3.931 > 2.365 ttable and has a significance value of 0.004 < 0.05. Simultaneously Current Ratio (CR) and Debt to Equity Ratio (DER) have a positive and significant effect on Return On Equity (ROE) with a significance value of 0.017 < 0.05 with a fcount value of 7.626 > ftable 4.74. At PT Telekomunikasi Indonesia (Persero) Tbk. The Coefficient of Determination (R Square) shows that the coefficient of determination of the variable Current Ratio and Debt to Equity Ratio to Return On Equity is 68.5%. While theremaining 31.5% is influenced by other variables.